Postmortem distribution pattern of morphine and morphine glucuronides in heroin overdose - Skopp, Gisela; Ganßmann, Beate; Mattern, Rainer; Aderjan, Rolf (International journal of legal medicine, 1996)
The postmortem distribution of morphine and its metabolites was investigated in four cases of heroin overdose to evaluate some of the factors that influence intravasal blood concentrations. Variables included were the chemical stability of morphine conjugates, hemoconcentration, incomplete distribution of the drug and diffusion processes. Blood samples from different sampling sites including the aorta, the infra- and suprarenal portion of the inferior vena cava, the superior vena cava, the femoral and subclavian veins, and the right and left ventricles were examined for morphine, morphine-3-glucuronide and morphine-6-glucuronide, hematocrit and water content. Drug concentrations were determined by HPLC based on the native fluorescence of the analytes. Morphine glucuronides proved to be stable for a time period of 72 h. The water content ranged from 65 to 83% and hematocrit values from 25 to 75%, and were seen as contributory factors to the dramatic differences observed for drug concentrations from different sampling sites. The differences could neither be attributed to incomplete distribution during life-time nor to a diffusion process following the different distribution volumes of morphine and its conjugates. A definite relationship between the ratio of the molar concentrations of morphine and its glucuronides, as assessed in pharmacokinetical studies after morphine dosing, could not be established. For a better understanding more cases and changes over time and tissue concentrations should be analysed.